Inventing the Pandemic Lifestyles: Bicycle Tourism during COVID-19 - Sujibto, B. J.; Arba'atun, Mira (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
The COVID-19 outbreak has harshly accelerated existing future of social life and changed how people approach and act toward it, including in the aspect of sport and tourism, that can be claimed to have created the pandemic's new social orders. This article, in essence, examines the cycling meanings and experiences of Yogyakarta’s cyclists in both individual and communal contexts during the pandemic. Having been categorized as an active sport which supports social and physical distance campaigns, the shift of meaning of cycle tourism both to increase immune system and to enjoy sightseeing at once is applied to critically explain the way people understand the cycling itself. In line with the motivational aspects, the meaning of cycling has shown fascinating facts shifted from regular sport to be more valuable due to disruptions during the pandemic. By applying qualitative descriptive methods, this research conducted observations and interviews with cyclists and cycling communities. This article shows two findings. First, the shift of meaning and awareness of cycling is considered as a pandemic sport because of a compatibility with its health protocols and as a sustainable tourism sector; and second, the emergence of cycle tourism as a pandemic lifestyle shaped constantly with social narratives of a pandemic. The psychological aspects have also become additional notes explained by this article.